1994
DOI: 10.1213/00000539-199403000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Concentrations of Edrophonium Enhance Desensitization of the Nicotinic Acetylcholine Receptor

Abstract: The principal acetylcholinesterase inhibitors used in clinical practice, edrophonium, neostigmine, and pyridostigmine, differ in their abilities to reverse profound neuromuscular block. This difference may reflect differential inhibition of the nicotinic acetylcholine receptor (nAChR) itself. To investigate this possibility, we studied the effects of these drugs on the function of nAChR (alpha 2 beta gamma delta subtype expressed in Xenopus laevis oocytes) using a whole-cell voltage clamp technique. All three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…21 Altered kinetics may result in a limited ability of edrophonium to effectively antagonize profound mivacurium-induced block. 21 Edrophoniuminduced desensitization of acetylcholine receptors 22 appears not to be a factor as other neuromuscular blockers in our study could be antagonized.…”
Section: Méthodementioning
confidence: 54%
“…21 Altered kinetics may result in a limited ability of edrophonium to effectively antagonize profound mivacurium-induced block. 21 Edrophoniuminduced desensitization of acetylcholine receptors 22 appears not to be a factor as other neuromuscular blockers in our study could be antagonized.…”
Section: Méthodementioning
confidence: 54%
“…However, McCartney et al [18] observed merely a reduced motor block onset time in their neostigmine group. Prolongation of the sensory block may be related to the newly discovered acetylcholine-mediated sensory regulatory mechanism controlled by the motor system [28], and the prolonged motor block may be the result of the nicotinic agonistic effect of neostigmine at the neuromuscular junction [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…ACAs have several limitations: they depend on the degree of neuromuscular blockade 40 (B); they have adverse effects on different organs and systems due to the antimuscarinic action; they have a ceiling effect 41 (D); they can lead to unpredictable reversal of neuromuscular blockade when used in patients with other comorbidities, or in situations such as hypothermia, or when using certain drugs such as calcium-channel blockers, aminoglycosides and magnesium sulphate 37 (D); and they can promote blockade by desensitization, with increased muscle weakness when used at high doses, or when used after complete recovery of neuromuscular blockade or without previous use of NMB 43 (C), 42,44 (D). They can also decrease the activity of the upper airway dilating muscles, if used after recovery of neuromuscular blockade induced by rocuronium 45 (B).…”
Section: How Can Porp Be Prevented?mentioning
confidence: 99%